Factor analysis of the most informative parameters affecting the efficiency of training wrestling students of physical education - S.V. Tkachenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Comprehensively analyzed the various factors that affect the absorption of the students practical course in wrestling. The study involved 98 boys - 3rd year students of the Faculty of Physical Education, who begin the study of the course Combating and methods of teaching. Also, 32 students who are engaged in the struggle. The results of studies of anthropometric, physical, functional, ergonomics students. The input data for the factor analysis were the first 3-ranking figure, biomechanical, physical fitness and functional status, anthropometric. It is established that the content of the first most significant factors included biomechanical parameters that demonstrate the value of balance and coordination abilities of others.